A method for quantitative acylcarnitine profiling in human skin fibroblasts using unlabelled palmitic acid: diagnosis of fatty acid oxidation disorders and differentiation between biochemical phenotypes of MCAD deficiency - Okun, Jürgen G.; Kölker, Stefan; Schulze, Andreas; Kohlmüller, Dirk; Vill, Katharina; Lindner, Martin; Hoffmann, Georg F.; Wanders, Ronald J. A; Mayatepek, Ertan (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2002)
Inherited disorders of fatty acid oxidation are a group of acute life-threatening but treatable disorders, clinically complicated by severe hypoketotic hypoglycemia precipitated by prolonged fasting. Among them, medium-chain acyl-CoA dehydrogenase (MCAD) deficiency is by far the most frequent disorder. Here we report a modified method for quantitative acylcarnitine profiling by electrospray ionisation-tandem mass spectrometry (ESI-MS-MS) in human skin fibroblasts using unlabelled palmitic acid as substrate. The reliability of this method was tested in cultured skin fibroblasts from previously diagnosed patients with specific carnitine cycle and fatty acid β-oxidation defects. Furthermore, acylcarnitine profiling was investigated in fibroblasts and dried blood spots from patients with different variants of MCAD deficiency. ESI-MS-MS-based investigation of cultured skin fibroblasts from patients with disorders of fatty acid oxidation revealed a pathognomonic acylcarnitine profiling. In addition, this method delineated different variants of MCAD deficiency, i.e. mild and classical. The octanoylcarnitine (C8)-to-decanoylcarnitine (C10) and C8-to-acetylcarnitine (C2) ratios were the most specific markers to differentiate mild and classical forms of MCAD deficiency in fibroblasts. Similar results were obtained by quantitative acylcarnitine profiling in dried blood spots. In conclusion, this novel technique is a powerful tool for the investigation of fatty acid oxidation disorders under standardized conditions in fibroblasts.